A review of a translational sociology: interdisciplinary perspective on politics and society - Xiao, Jiayan; Bai, Yang; Li, Chili (Frontiers in Psychology, 2023)
A Translational Sociology—Interdisciplinary Politics and Society by Esperança Bielsa in 2023 has aroused our great interest, as the title has explicitly indicated a further fulfillment and development of Translational Sociology from the perspective of interdisciplinary politics and society. The recent decade witnesses how Translational Sociology is well-received in China, the further exploration of translation and society, translation and politics, translation and experience in this book enables more teachers, researchers, and postgraduates in translation study to be fully aware of the diversity, complexity, and modernity of translation as a social practice. Moreover, by reinforcing the core role of translation in mediating language differences in all aspects of social life, questioning simplistic views of cultural homogenization, probing into the identity and transformation, politics and democracy, and the nature of modern experience in translating, this book updates our comprehension of the global characteristics of contemporary society from the perspective of translation study.